Dichlorido{4-cyclohexyl-1-[1-(2- hyridyljN)ethylidene]thiosemicarbazidatoj2 N1 ,S}phenyltin(IV) - Fasihuddin B., Ahmad; Md. Abdus, Salam; Md. Abu, Affan; M. Ibrahim Mohamed, Tahir; Edward R. T., Tiekink (International Union of Crystallography, 2010)
The SnIV atom in the title compound, [Sn(C6H5)(C14H19- N4S)Cl2], exists within a distorted octahedral geometry defined by the N,N0 ,S-tridentate monodeprotonated Schiff base ligand, two mutually trans Cl atoms, and the ipso-C atom of the Sn-bound phenyl group; the latter is trans to the azo-N atom. The greatest distortion from the ideal geometry is found in the nominally trans angle formed by the S and pyridyl-N atoms at Sn [151.03 (4)]. With the exception of the cyclohexyl group (chair form), the Schiff base ligand is almost planar (r.m.s. deviation of non-H and Sn atoms = 0.053 A˚ ). The nearly orthogonal orientation of the Sn-bound phenyl group [N—Sn—C—C torsion angle = 70.8 (5)] to the planar portion of the Schiff base allows for the formation of significant intramolecular C—HCl interactions which preclude the Cl atoms from participating in N—HCl hydrogen bonds. Instead, C—H contacts, involving methylene H and the Sn-bound phenyl group, lead to the formation of supramolecular chains that pack in the bc plane. Connections between these layers are of the type C—HCl.